Chaos Synchronization of the Fractional Order Time Delay System - Cetintas, Gulten; Celik, Vedat (Ieee, 2015)
In this paper, the chaos synchronization of two identical fractional order time delay system (One Master-Transmitter, other Slave-Receiver) has been achieved for different initial conditions. For achieving synchronization between two systems, a proportional controller has been designed by using active control method. Efficiency of the controller designed has been tested using modified Mikhailov stability criterion and its appropriate gain parameter has been selected. The obtained results have been verified by the time domain simulations of the system.
9th International Conference on Electrical and Electronics Engineering (ELECO) -- NOV 26-28, 2015 -- Bursa, TURKEY
Keywords: Behavior